Treatment Determinants Influence the Health of Tuberculosis Patients - Dian Pratiwi; Mappeaty Nyorong; Ismail Efendy; Indah Anggraini; Thomson Nadapdap (Jurnal Perilaku Kesehatan Terpadu, 2022)
Tuberculosis is a bacterial infection caused by Mycobacterium tuberculosis. TB is the world's tenth biggest cause of mortality, with an estimated 1.3 million tuberculosis patients dying each year. This study aims to determine and analyse the determinants of treatment that affect the healing of Tuberculosis Patients in the Karang Anyar Health Centre Work Area, Beringin District, Deli Serdang Regency. The research design used was an analytic survey with a cross sectional design. The research sample was all 44 people with pulmonary TB who had recovered. Data analysis with chi square test and multiple logistic regression test. From 44 respondents, it was found that the results of the TB patient healing study had a significant relationship with the results of the Logistics Regression Test on the PMO variable (p=0.004, OR=1.332), contact history (p=0.004, OR=2.001), medication adherence (p=0.001, OR=27,267), education level (p=0.002,OR=2,998), knowledge (p=0.003,OR=6.334), nutritional status (p=0.000,OR=5,333), religious (p=0.001,OR=9,445) and the most dominant factor was medication adherence (OR=27,267). Compliance with treatment affects the cure for tuberculosis where there is family support, patients are motivated to recover and routinely carry out treatment. It is expected that all tuberculosis sufferers to consume a balanced nutritional diet, perform treatment obediently and have good faith and knowledge as an effort to cure tuberculosis.